The COST 732 Best Practice Guideline for CFD simulation of flows in the urban environment: a summary. (8th February 2011) - Franke, Jorg; Hellsten, Antti; Schlunzen, K. Heinke; Carissimo, Bertrand
This paper is a summary of the "Best Practice Guideline" (BPG) document (Franke et al., 2007) produced in the framework of the European COST Action 732 "Quality assurance and improvement of micro-scale meteorological models", available from the site given in the reference section. The full document provides guidelines for undertaking simulations that are used to evaluate micro-scale obstacle-accommodating meteorological models. This paper provides an overview of the topics covered in the full document without reproducing the specific recommendations.